2020
DOI: 10.1177/1354066120930801
|View full text |Cite
|
Sign up to set email alerts
|

The prejudice first model and foreign policy values: racial and religious bias among conservatives and liberals

Abstract: Scholars who study public opinion and American foreign policy have accepted what Rathbun et al. (2016) call the “Vertical Hierarchy Model,” which says that policy attitudes are determined by more abstract moral ideas about right and wrong. This article turns this idea on its head by introducing the Prejudice First Model, arguing that foreign policy preferences and orientations are driven by attitudes toward the groups being affected by specific policies. Three experiments are used to test the utility of this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…We also carry out a similar analysis with North Korea, with specializing in East Asia being the relevant measure of expertise. The selection of endogenous and exogenous variables is based on the theory that more abstract moral beliefs affect more concrete political views, while also influencing perceptions of threat (Hanania and Trager 2019;Rathbun et al 2016). The inclusion of belief about the aggressive intentions of the actor in question, measured on a scale from 1 to 7, is included as it is one plausible pathway through which expertise influences political views.…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also carry out a similar analysis with North Korea, with specializing in East Asia being the relevant measure of expertise. The selection of endogenous and exogenous variables is based on the theory that more abstract moral beliefs affect more concrete political views, while also influencing perceptions of threat (Hanania and Trager 2019;Rathbun et al 2016). The inclusion of belief about the aggressive intentions of the actor in question, measured on a scale from 1 to 7, is included as it is one plausible pathway through which expertise influences political views.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Finally, this paper raises deep questions about the nature of expertise in the modern world. It is quite striking that, even among those with similar levels of education and who spend their time researching similar issues, moral values regarding the US and its place in the world not only drive opinions on specific issues but even perceptions of threat (see Hanania and Trager 2019). While the desire to bring more expertise into the policy making arena can be perceived as a matter of simply introducing technocratic knowledge into public discussions, at its heart the project is political in nature, as one group of experts can only gain influence at the expense of others.…”
Section: Discussionmentioning
confidence: 99%
“…The two experiments also share some commonalities that may lead to questions about the generalizability of the results: namely, the subjects are white males who violated left wing taboos. Since prejudices based on race, gender and political affiliation are found throughout social psychology, it is plausible that the identities of the public figures or the nature of either controversy helped drive the result (Hanania & Trager, 2019), although the fact that women and liberals in particular became more likely to want to punish after hearing about an apology argues against this possibility. More research is needed before firm conclusions can be drawn about when apologies have no effect and when they increase or reduce the desire on the part of observers to punish the figure embroiled in controversy.…”
Section: Discussionmentioning
confidence: 99%
“…One reported that activating Christian concepts increases racial prejudice (henceforth, the "Christianprejudice" findings; M. K. Johnson et al, 2010), and the other reported that children with same-sex parents are no worse off than children with opposite-sex parents (henceforth, the "same-sex-parents" findings; Wainright et al, 2004). We selected these articles because they address matters of Christianity and same-sex parenting, which tend to be of greater concern for people who are more conservative (Crawford et al, 2013;Hanania & Trager, 2021).…”
Section: Methodsmentioning
confidence: 99%